Strategies for Improving the Economy of Creative MSMEs Communities in Bamboo Crafts in Binjai City from an Islamic Economic Perspective - Anggia Nurulita; Nurbaiti Nurbaiti; Muhammad Ikhsan Harahap (Al-Muamalat: Jurnal Ekonomi Syariah, 2024)
In developing countries, MSMEs represent the largest economic sector capable of absorbing a significant proportion of the labor force. Currently, MSMEs are driven by a wave of creative economy that transforms natural resources that have no economic value into high-value products. As a result, people's income increases due to this economic activity. One of the creative MSMEs, the bamboo craft industry in Binjai city, is known as the center of the bamboo craft industry. However, the overall income of MSME players in the area has not shown a significant increase. This research aims to analyze the business strategies used and view them from an Islamic economic perspective. The research method is qualitative research with a SWOT analysis. Primary data was obtained from 10 bamboo craft MSME players in Binjai, while secondary data came from scientific publications and BPS of Binjai city. The results indicated that the business strategy employed by bamboo craft MSMEs in Binjai City is consistent with Islamic economic principles. The strategy derived from the SWOT analysis is the SO strategy, which focuses on capitalizing on market opportunities and optimizing strengths for product development. This research offers insights into how the creative economy can drive MSMEs and enhance community income, as well as how business strategies can be aligned with Islamic economic values to achieve sustainable success.